Catch as cat can [large type] - Brown, Rita Mae (Brown, Rita Mae. Mrs. Murphy mystery., 2002)
It was the second body that aroused suspicion. The first victim, Roger O'Bannon, had a fast-and-loose life style that would have killed a lesser man. But when Mary Minor "Harry" Haristeen hears that a second corpse has turned up, she begins to suspect that the high mortality rate in Crozet, Virginia, is not exactly natural. Of course, Haristeen's investigations are enhanced once again by her very active feline menagerie, including the peerless "Mrs. Murphy."